In vitro Suppression of Prolactin During Later Stages of Egg Lay in Domestic Hen (Gallus gallus Domesticus) Anterior Pituitcytes by RNA Interference - Reddy , I.J.; Mishra, Ashish; Mondal, S.; Murthy, H.N.N. (International Journal of Poultry Science, 2013)
Prolactin (PRL) is a peptide hormone secreted by anterior pituitary gland. PRL increases as per the age and reproductive cycle of birds from normal physiological levels to extremely higher level there by affecting the ovulation, egg formation, oviposition, egg production and hyperprolactinemia. This is more pronounced and persistent after 72 weeks of age in birds. Hence a study was conducted in anterior pituitary primary cultured cells obtained from 72 and 82 weeks old white leg horn (WLH) hens to knock down the PRL gene expression by siRNA and observing its effects on PRL, PRL mRNA, protein content of PRL, prolactin receptor (PRLR) and Growth Hormone (GH) mRNA to unravel the functional role of PRL at 72 and 82 week age by siRNA for PRL. Three siRNAs were designed as per standard siRNA protocols and studied the suppression of PRL gene expression in primary cultured cells procured from adult chicken anterior pituitary glands in in vitro conditions. Average percentage reduction of PRL in anterior pituitary primary cell culture following siRNA transfection was 82 and 60% at 72 and 82 weeks respectively. Protein content of PRL was significantly (p